Selective targeting of mutually exclusive DNA G-quadruplexes: HIV-1 LTR as paradigmatic model. Issue 9 (13th April 2020) - Tassinari, Martina; Zuffo, Michela; Nadai, Matteo; Pirota, Valentina; Sevilla Montalvo, Adriana Carolina; Doria, Filippo; Freccero, Mauro; Richter, Sara N
Abstract: Targeting of G-quadruplexes, non-canonical conformations that form in G-rich regions of nucleic acids, has been proposed as a novel therapeutic strategy toward several diseases, including cancer and infections. The unavailability of highly selective molecules targeting a G-quadruplex of choice has hampered relevant applications. Herein, we describe a novel approach, based on naphthalene diimide (NDI)-peptide nucleic acid (PNA) conjugates, taking advantage of the cooperative interaction of the NDI with the G-quadruplex structure and hybridization of the PNA with the flanking region upstream or downstream the targeted G-quadruplex. By biophysical and biomolecular assays, we show that the NDI-PNA conjugates are able to specifically recognize the G-quadruplex of choice within the HIV-1 LTR region, consisting of overlapping and therefore mutually exclusive G-quadruplexes. Additionally, the conjugates can induce and stabilize the least populated G-quadruplex at the expenses of the more stable ones. The general and straightforward design and synthesis, which readily apply to any G4 target of choice, together with both the red-fluorescent emission and the possibility to introduce cellular localization signals, make the novel conjugates available to selectively control G-quadruplex folding over a wide range of applications.